2020
DOI: 10.1177/2150135120945688
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Complications Following Unifocalization and Pulmonary Artery Reconstruction Procedures

Abstract: Background: Unifocalization and pulmonary artery reconstructions have been developed to treat complex disorders of pulmonary artery development. These procedures require extremely long periods of cardiopulmonary bypass (CPB) to facilitate surgical repair. The objective of this study was to document the prevalence of complications in patients undergoing unifocalization or pulmonary artery reconstructions associated with prolonged periods of CPB. Methods: This was a retrospective review of 100 consecutive patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…For example, patients experiencing a cardiac arrest and/or who require cannulation for extracorporeal membrane oxygenator will be impacted in a more significant manner than patients who undergo a single bronchoscopy or delayed sternal closure. In a previous study evaluating the prevalence of complications in patients undergoing complex pulmonary artery reconstructions, we found that six complications had a significant impact on hospital length of stay 9 . These six complications included major adverse cardiac events (+35 days), unplanned major reoperation (+20 days), pneumonia (+15 days), re‐intubation (+14 days), bleeding (+11 days), and pleural effusion (+6 days).…”
Section: Discussionmentioning
confidence: 96%
“…For example, patients experiencing a cardiac arrest and/or who require cannulation for extracorporeal membrane oxygenator will be impacted in a more significant manner than patients who undergo a single bronchoscopy or delayed sternal closure. In a previous study evaluating the prevalence of complications in patients undergoing complex pulmonary artery reconstructions, we found that six complications had a significant impact on hospital length of stay 9 . These six complications included major adverse cardiac events (+35 days), unplanned major reoperation (+20 days), pneumonia (+15 days), re‐intubation (+14 days), bleeding (+11 days), and pleural effusion (+6 days).…”
Section: Discussionmentioning
confidence: 96%
“…In a study of 100 patients undergoing complex pulmonary artery reconstructions with cardiopulmonary bypass times in excess of 300 min, the median number of complications was 4, and median hospital length of stay was 24 days. 36 Thus, this may be the “price” that one must pay for performing procedures with very long cardiopulmonary bypass times (there was a sole mortality resulting in a 99% rate of survival to discharge). In the current study, there were 2 patients with a history of sudden cardiac arrest in whom the decision was made preoperatively not to address the presence of concomitant peripheral pulmonary artery stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…2 This anatomic variability becomes clinically relevant when MAPCAs are used in the reconstruction of a pulmonary vascular bed. [3][4][5][6][7][8][9] Many groups have adopted the "unifocalization" of MAPCAs for the treatment of PA/VSD/MAPCAs. [10][11][12][13] One anatomic variation of MAPCAs is those that traverse behind the esophagus en route to the lung parenchyma.…”
Section: Introductionmentioning
confidence: 99%
“…2 This anatomic variability becomes clinically relevant when MAPCAs are used in the reconstruction of a pulmonary vascular bed. 39 Many groups have adopted the “unifocalization” of MAPCAs for the treatment of PA/VSD/MAPCAs. 1013…”
Section: Introductionmentioning
confidence: 99%